T cell replicative senescence in human aging - Chou, Jennifer P; Effros, Rita B (Current pharmaceutical design, 2013)
The decline of the immune system appears to be an intractable consequence of aging, leading to increased susceptibility to infections, reduced effectiveness of vaccination and higher incidences of many diseases including osteoporosis and cancer in the elderly. These outcomes can be attributed, at least in part, to a phenomenon known as T cell replicative senescence, a terminal state characterized by dysregulated immune function, loss of the CD28 costimulatory molecule, shortened telomeres and elevated production of proinflammatory cytokines. Senescent CD8 T cells, which accumulate in the elderly, have been shown to frequently bear antigen specificity against cytomegalovirus (CMV), suggesting that this common and persistent infection may drive immune senescence and result in functional and phenotypic changes to the T cell repertoire. Senescent T cells have also been identified in patients with certain cancers, autoimmune diseases and chronic infections, such as HIV. This review discusses the in vivo and in vitro evidence for the contribution of CD8 T cell replicative senescence to a plethora of age-related pathologies and a few possible therapeutic avenues to delay or prevent this differentiative end-state in T cells. The age-associated remodeling of the immune system, through accumulation of senescent T cells has farreaching consequences on the individual and society alike, for the current healthcare system needs to meet the urgent demands of the increasing proportions of the elderly in the US and abroad.